IDENTIFIKASI KARAKTERISTIK MATERIAL DARI BAHAN BATIK TRADISIONAL INDONESIA - Ryanu, Harfan Hian; Jumria, Ummi; Siddik, Hawary; Hamsy, Muhammad Daffa; Damayanti, Nabila Rizqa; Fauziah, Regita Nurul; Nugroho, Bambang Setia; Nur, Levy Olivia (Telkom University, 2023)
Wearable antenna has an important role in WBAN (Wireless Body Area Network) as the main component that supports on-body communication. This study focuses on the characterization of Material Under Test (MUT) from Indonesian traditional batik material using the CSRR (Complementary split ring resonator) sensor extraction method. The frequency response and magnitude of S21 are used to extract the relative permittivity and loss tangent of the material. From all the responses that appear, a simulation and measurement of wearable antennas is carried out with a working frequency of 2.4. GHz. The antenna with the most similar simulation and measurement results is then selected as a candidate for relative permittivity and loss tangent of the material. From all the 6 frequency responses that emerged from CSRR sensor measurements, the relative permittivity value of 2.083 and the loss tangent of 0.144 achieved a good similarity between the measurement and simulation with an accuracy rate of 99.17%. The final design of the proposed wearable antenna is also validated to transmit heart rate data using the ESP32 microcontroller to the internet using a 2.4 GHz frequency Wifi access point. Key Words: Wearable antenna, extraction of material characteristics, wireless body area network (WBAN), CSRR, material under test, vital signs